Acute Liver Failure Secondary to Remdesivir in the Treatment of COVID-19. Issue 10 (6th October 2022) - Lin, Kevin; Gausman, Valerie; Poles, Michael; Popov, Violeta
ABSTRACT: Remdesivir has been the mainstay of coronavirus disease 2019 treatment since the start of the severe acute respiratory syndrome coronavirus 2 pandemic. Despite its growing use, safety data are limited. We present the case of an elderly man with obesity and coronavirus disease 2019 who developed acute liver failure after initiation of remdesivir. This report broadens our knowledge of the side effect profile of remdesivir and discusses potential risk factors and an approach to remdesivir-induced liver failure. Our case also highlights the importance of monitoring hepatic function after initiation of therapy with remdesivir.